Dynamic fracturing properties of marble after being subjected to multiple impact loadings. (1st May 2020) - Yu, Liyuan; Fu, Anqi; Yin, Qian; Jing, Hongwen; Zhang, Tao; Qin, Hao
Highlights: Dynamic peak stress and elastic modulus degrade with an increasing impact number. Dynamic fracture toughness and fracture energy decrease as dynamic damage increases. The fractal dimension of the crack path increases linearly with dynamic damage. The larger the dynamic damage of the specimen is, the rougher the fracture surface. Abstract: A multiple impact loading test was conducted on notched semi-circular bend (NSCB) marble specimens by using a split Hopkinson pressure bar (SHPB) apparatus. Then, specimens with various dynamic cumulative damages were subjected to dynamic three-point bending loading. During the multiple impact loading test, the dynamic incident energy was kept constant in each impact. The dynamic peak stress and the elastic modulus degrade gradually with an increasing impact number. In the dynamic three-point bending test, the dynamic fracture toughness and the fracture energy of the specimens decrease gradually with increasing dynamic cumulative damage, and the maximum declines are 65.27% and 76.23%, respectively. In terms of the failure modes, the fractal dimension of the crack propagation path increases approximately linearly with the dynamic cumulative damage, namely, the crack propagation path becomes increasingly tortuous. According to the quantitative analysis of the fracture surface roughness, the larger the dynamic cumulative damage of the specimen is, the rougher the fracture surface, and the larger the area of the fracture surface. These results can improve the understanding of the dynamic fracturing properties of rock structures after multiple impact loadings.